I would choose to solve this problem as follows:
The ant's absolute speed is:
[MATH]v=1+y[/MATH]
The ant's speed is it own relative to the band plus the portion of the band it has already traveled times the rate the band is being stretched.
Hence, we can arrange this as a linear first order ODE:
[MATH]\d{x}{t}-\frac{1}{t+2}x=1[/MATH]
Compute integrating factor:
[MATH]\mu(t)=\exp\left(-\int \frac{1}{t+2}\,dt\right)=\frac{1}{t+2}[/MATH]
[MATH]\frac{1}{t+2}\d{x}{t}-\frac{1}{(t+2)^2}x=\frac{1}{t+2}[/MATH]
[MATH]\frac{d}{dt}\left(\frac{1}{t+2}x\right)=\frac{1}{t+2}[/MATH]
Integrate:
[MATH]\frac{1}{t+2}x=\ln(t+2)+C[/MATH]
[MATH]x(t)=(t+2)(\ln(t+2)+C)[/MATH]
[MATH]x(0)=2(\ln(2)+C)=0\implies C=-\ln(2)[/MATH]
And so we find:
[MATH]x(t)=(t+2)(\ln(t+2)-\ln(2))[/MATH]
This does imply:
[MATH]y=\ln(t+2)-\ln(2)\implies y'=\frac{1}{t+2}[/MATH]
But, I don't think I would have thought to begin with that. And then to finish:
[MATH]y=\ln(t+2)-\ln(2)=1\implies \frac{t+2}{2}=e\implies T=2e-2[/MATH]